2022
DOI: 10.1021/acs.est.2c06167
|View full text |Cite
|
Sign up to set email alerts
|

Microscale Spatiotemporal Variation and Generation Mechanisms of Reactive Oxygen Species in the Rhizosphere of Ryegrass: Coupled Biotic–Abiotic Processes

Abstract: Reactive oxygen species (ROS) play key roles in soil biogeochemical processes, yet the occurrence and accumulation of ROS in the rhizosphere are poorly documented. Herein, we first developed a ROS-trapping membrane to in situ determine ROS in the ryegrass rhizosphere and then quantified the temporal and spatial variations of representative ROS (i.e., O 2•� , H 2 O 2 , and • OH). Fluorescence imaging clearly visualized the production of ROS in the rhizosphere. Both O 2•� and H 2 O 2 content increased first and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…In contrast, perfluorooctane amide amine oxide (PFOANO) and PFOSNO, both containing terminal amine oxide moieties, underwent more pronounced and extensive abiotic transformation in sterilized soil, resulting in the terminal products of perfluorooctane amide propionic acid and FOSA, respectively . The differences in abiotic degradation behavior between ECF-based amine oxides in soil and 6:2 FTNO in sludge can be attributed to the abundant natural organic matter and iron minerals present in the soil, which are known to facilitate the production of ROS, thereby promoting the chemical degradation of FOSA-based amine oxides. …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, perfluorooctane amide amine oxide (PFOANO) and PFOSNO, both containing terminal amine oxide moieties, underwent more pronounced and extensive abiotic transformation in sterilized soil, resulting in the terminal products of perfluorooctane amide propionic acid and FOSA, respectively . The differences in abiotic degradation behavior between ECF-based amine oxides in soil and 6:2 FTNO in sludge can be attributed to the abundant natural organic matter and iron minerals present in the soil, which are known to facilitate the production of ROS, thereby promoting the chemical degradation of FOSA-based amine oxides. …”
Section: Resultsmentioning
confidence: 99%
“…We have previously found that Fe-based nanomaterials assisted plant rhizoremediation of PCB-contaminated soil . Meanwhile, it was recently demonstrated that the plant rhizosphere is a ubiquitous but generally unrecognized hotspot for ROS production. , It is well-known that the occurrence of biogenic free radicals is a widespread biogeochemical process that can modulate the fate of pollutants. This study not only demonstrates the ability of PGPR extracellular ROS to degrade organic pollutants but also illustrates the significant contribution of nZVI to accelerate this process.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…Therefore, we hypothesize that iron plaque can reduce oxygen secreted by the roots to produce ·OH. Though the production of ·OH in rhizosphere has been reported, , the role of iron plaque in ·OH production and the characteristics of ·OH produced by iron plaque remain unknown. Since the iron plaque is a significant heterogeneous interface between the root and soil, the production of ·OH by iron plaque may be distinct from the production of ·OH by the bulk phase of rhizosphere.…”
Section: Introductionmentioning
confidence: 99%